2023
DOI: 10.1002/ana.26722
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Aquaporin‐4‐IgG Serostatus in 986 Patients: A Laboratory‐Based Longitudinal Analysis

Masoud Majed,
Cristina Valencia Sanchez,
Jeffrey L. Bennett
et al.

Abstract: ObjectiveThis study was undertaken to investigate factors associated with aquaporin‐4 (AQP4)‐IgG serostatus change using a large serological database.MethodsThis retrospective study utilizes Mayo Clinic Neuroimmunology Laboratory data from 2007 to 2021. We included all patients with ≥2 AQP4‐IgG tests (by cell‐based assay). The frequency and clinical factors associated with serostatus change were evaluated. Multivariable logistic regression analysis examined whether age, sex, or initial titer was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, some patients may become at least temporarily antibody-negative with B-cell-directed therapies or anti-IL-6-R therapy over time. Recently one large study (933 initially AQP4-gG positive patients) demonstrated that seroreversion is rare (11%), occurs predominantly in younger patients (age < 20 years) and in patients with initially low AQP4-IgG titers and is often transient [ 139 ]. Patients who serorevert are still considered AQP4-IgG-positive NMOSD cases, as in the RIN-1 trial.…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…However, some patients may become at least temporarily antibody-negative with B-cell-directed therapies or anti-IL-6-R therapy over time. Recently one large study (933 initially AQP4-gG positive patients) demonstrated that seroreversion is rare (11%), occurs predominantly in younger patients (age < 20 years) and in patients with initially low AQP4-IgG titers and is often transient [ 139 ]. Patients who serorevert are still considered AQP4-IgG-positive NMOSD cases, as in the RIN-1 trial.…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Indeed, over 3.7 years, one third of the treated AQP4+ NMO patients seroreverts to AQP4 negative. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a strong diagnostic suspicion and a negative test result, repeat testing in specialized laboratories on stored samples obtained acutely is reasonable. Repeat testing over time (eg, after 1 to 2 years) may also be considered in highly suspected cases as seroconversion to positivity after an initially negative test result may occur in both diseases in a minority of patients 64 . Serum positivity for AQP4 IgG usually persists over time with minimal titer fluctuations, 64 which facilitates the diagnosis in patients evaluated years after disease onset.…”
Section: Diagnosismentioning
confidence: 99%
“…Repeat testing over time (eg, after 1 to 2 years) may also be considered in highly suspected cases as seroconversion to positivity after an initially negative test result may occur in both diseases in a minority of patients 64 . Serum positivity for AQP4 IgG usually persists over time with minimal titer fluctuations, 64 which facilitates the diagnosis in patients evaluated years after disease onset. Conversely, patients with MOG IgG may become seronegative over time, which may limit the diagnosis outside of the acute setting 55 .…”
Section: Diagnosismentioning
confidence: 99%